From Knowledge to Fintech: Drivers of Generation Z’s Investment Interest - Gracia, Olivia; Champaca, Mychelia (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2025)
The rapid growth of financial technology and the increasing accessibility of investment platforms have transformed how young generations approach financial decisions, making it essential to understand the factors that drive their investment behavior. This study aims to examine the influence of investment knowledge, investment risk perception, and financial technology on the investment intention of Generation Z. Using a quantitative research design, 120 respondents from Generation Z were selected through a non-probability purposive sampling method. Data were collected using questionnaires that met validity and reliability criteria, then analyzed using multiple linear regression after passing classical assumption tests. The results indicate that investment knowledge and financial technology both have a positive and significant effect on investment intention, suggesting that greater understanding and digital accessibility encourage participation in investment activities. Conversely, investment risk perception shows a negative and significant effect, implying that higher perceived risks may discourage potential investors. These findings highlight the need for targeted financial education and the optimization of fintech tools to reduce perceived barriers, thereby fostering stronger investment engagement among young generations in the digital era.